Factors influencing purchase intention based on facebook advertising: A study on generation Y consumers in UUM - Nik Muhammad Ismail, Karim (2015)
This purpose of this paper to is to discuss the phenomenon of social media advertising, and investigate the effectiveness of social media advertising on Malaysian Generation Y consumers. The framework as described in the study is adopted from the new model of website advertising effectiveness proposed by a group of Macedonian researchers in 2009. The significance of this study is to illustrate the idea how businesses can strategize on how they can improve their advertisement on social media by improving purchase intention towards their products. For this purpose, the study was focused on advertising on one of the most popular social media platforms, namely Facebook, on Malaysian Generation Y consumers. They study embarked to find out the relationship between Facebook advertising attributes, Facebook page credibility, and communication towards purchase intention. A quantitative study was employed using questionnaire-based survey. The survey took place in Universiti Utara Malaysia, where it received participation from 200 respondents. Data gathered from the survey were analyzed with Pearson correlation coefficient, using SPSS 2, in order to test the hypothesis. The study found that Facebook advertising attributes, Facebook Page credibility and communication have positive relationships towards purchase intention. The study contributes on how businesses can strategize their advertisement on Facebook by putting emphasis on the factors that influences purchase intention.